English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5 answers

2 y = x + 4
2 y = 14 s + 2
14 s + 2 = x + 4
14 s = x + 2
s = (1/14) (x + 2)

2007-11-03 00:51:28 · answer #1 · answered by Como 7 · 0 1

x=2y-4
=>x+4=2y
=>y=(x+4)/2


:.(y=7s+1)=((x+4))/2=7s+1)
=>x+4=14s+2
=>x+4-2=14s
=>s=x/14+1/7


This is 's' in terms of 'x'.

2007-11-03 04:23:57 · answer #2 · answered by Kumara 2 · 0 0

x+4=2y 7s+1=y
x+4=2y 14s+2=2y
then(transitive property)
x+4= 14s +2
x-14s= -2
x=14s-2

2007-11-03 03:50:06 · answer #3 · answered by Anonymous · 0 0

since y = 7s + 1, then substitute it in the x equation

x = 2(7s + 1) -4
x = 14s + 2 - 4
x = 14s -2 <=== answer

2007-11-03 03:48:51 · answer #4 · answered by Lotus 4 · 0 0

this is one of those "plug it in" problems

2(7s+1) - 4 = x

14s+2 - 4 = x

14s - 2 = x

not sure how much further u wanna go with that

2007-11-03 03:45:47 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers